Contribution to the knowledge of the apterous genus Zubovskya Dovnar-Zapolskij, 1932 (Orthoptera: Acrididae: Melanoplinae). Taxonomic composition, notes on Zubovskya koeppeni (Zubovsky, 1900), and entomogeographic studies on Z. mongolica Storozhenko, 1986 - Sergeev, Michael G.; Molodtsov, Vladimir V. (Zootaxa, 2025)
Taxonomic status and composition of the genus Zubovskya Dovnar-Zapolskij, 1932 are discussed. The following synonymy is proposed: Zubovskya koeppeni koeppeni (Zubovsky, 1900) = Zubovskya eyouqiensis Li, Li & Yin, 2015, syn. nov. and Zubovskya koeppeni parvula (Ikonnikov, 1911) = Zubovskya xiai Li, Li & Yin, 2015, syn. nov. Distribution patterns of the rare apterous grasshopper Zubovskya mongolica Storozhenko, 1986 are revealed. The species is known only from several localities with geographic coordinates determined. Its populations are characterized by relatively low abundance and are found at altitudes exceeding 1700 m. Their contemporary conservation status currently does not raise any serious concerns. However, if the global warming trend continues, the areas suitable for the existence of the species will be significantly reduced, since the axial parts of the local ridges are mainly located at altitudes between 1800 and 2500 m.